Niger : Beyond Connections - Energy Access Diagnostic Report Based on the Multi-Tier Framework - Brutinel, Marina (World Bank, Washington, DC, 2020)
Niger is a vast, landlocked, and mostly arid Sub-Saharan country, located in the heart of the Sahel region, with a rapidly growing population, estimated at 22.4 million (World Bank 2018a), of which the majority lives in rural areas. Despite considerable progress in the area of poverty reduction, extreme poverty remains very high, at an estimated 41.5 percent in 2019, affecting more than 9 million people in a country prone to climate risk and insecurity. The World Bank, with support from the Energy Sector Management Assistance Program (ESMAP), has launched the Global Survey on Energy Access, using the Multi-Tier Framework (MTF) approach. The survey’s objective is to provide more nuanced data on energy access, including access to electricity and cooking solutions. The MTF approach goes beyond the traditional binary measurement of energy access, for example, ‘having or not having’ a connection to electricity, ‘using or not using’ clean fuels in cooking, to capture the multidimensional nature of energy access and the vast range of technologies and sources that can provide energy access, while accounting for the wide differences in user experience.